Spontaneous leaflet fracture resulting in embolization from mechanical valve prostheses - van Steenbergen, Gijs G.J. (J Card Surg, 2018)
Spontaneous leaflet fracture of mechanical heart valve prostheses is very rare. We describe a case of spontaneous leaflet embolization 31 years after aortic valve replacement with an Edwards‐Duromedics prosthesis (Baxter Healthcare Corp., Edwards Division, Santa Ana, CA). We review the literature on this subject to increase awareness and recognition for this potentially life‐threatening complication.